The Business Knowledge Training Needs of South African Biokineticists to Ensure Business Sustainability - Lumb, Michael James (The IIE, 2020)
Business knowledge training is essential to succeed in the modern era. Health and medical professionals are exposed to knowledge that allows them to treat pathologies, but it would seem little effort is given towards preparing health and medical professionals to manage businesses in a sustainable, effective, and efficient manner. The following study examined the business knowledge training needs of South African Biokineticists, a health profession that is a part of the Health Professions of South Africa (HPCSA). The approach to examining the problem included identifying and conducting deductive research on previous literature that explored similar problems amongst different health and medical professionals including American Chiropractors and South African Audiologists. In order to collect the required data an online questionnaire was developed and distributed through the Biokinetics Association of South Africa (BASA) to its members. The reason for using an online based questionnaire was due to the low cost for distribution, respondents could complete the questionnaire in their own convenient time, and it excludes researcher bias and pressure. It was also in regulation with COVID-19 protocols. A quantitative, cross-sectional, deductive, and combination of descriptive and inferential research design was used for this study. 69 Biokineticists responded to the questionnaire. Combined high to very high needs for the business knowledge areas explored were: Accounting: 27.5%, Business Sustainability: 33.3%, Corporate Social Responsibility: 23.2%, Ethics: 55%, Financial Management: 34.7%, Human Resource Management: 28.9%, Leadership and Managerial Decision Making: 43.4%, Marketing: 40.6%, Operational Management: 39.1% and, Strategic Management: 33.3%. 70.6% per cent of the participants who partook in the study suggested they needed other business knowledge training needs by providing suggestions in the final question. Of the 70.6%, the most standout requests included information technology (17.02%), Tax related management and knowledge (19.15%) and medical aid training for ICD-10 coding (12.77%). The other 51.06% of the participants that answered the final question provided suggestions that could be categorised into the areas of business already reported on in the Likert Scale.
Keywords: Business knowledge; Biokinetics; Training needs; Health; Medical professionals